Branding BRANDING MANAGEMENT: MEMBENTUK TALENTA UNGGUL MELALUI KESISWAAN MADRASAH IBTIDAIYAH - Aufani, Nabil Achmad; Muhairira, Nurjamilatul; Minnah, Ariny Tamamul; Fatiq, Diskan Firzan Nadia; Susilawati, Samsul (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2025)
Branding is a strategic instrument in building the reputation and quality of the institution. MI Islamiyah Malang, as an Islamic educational institution, has great potential in strengthening branding. This study uses a qualitative approach with observation, interview, and documentation data collection techniques, and uses the data analysis of the Miles and Huberman model including data reduction, data presentation, conclusion/verification, data wetness using triangulation of sources and methods. The results of the study show that branding is developed through student management and the formation of superior talents through 21st century skills-based extracurricular activities. Critical thinking honed through the Olympics; collaboration through futsal and banjari; communication through English clubs, tahfidz, and storytelling; creativity through MTQ and coloring; culture through dance and Pagar Nusa; and connectivity through coding and robotics. Extracurricular management refers to the 6M management concept: man, method, money, material, machine, and market. MI Islamiyah presents expert teachers, provides allowances, provides adequate facilities, conducts routine evaluations, and carries the slogan